Моя Родина - Россия. - Михалков Сергей Владимирович (Моя страна, 2006)
Экземпляры: (2009) / Инвентарный номер: 45905 / Цена: 150.00 / Сис.шифр: 63.3(2) мл / Авт.знак: М 69 / ГРНТИ: 03 / ББК: 63.3(2) мл